Combination effects of roof coating and solar photovoltaic system in the tropical region of Ghana: A case study. Issue 5 (September 2019) - Opare, Wisdom; Kang, Can; Gu, Yiping; Mao, Ning
A combinative use of the photovoltaic modules and roof coating on building was implemented for an institutional hall in Ghana. Computational fluid dynamics simulation was performed for both coated and uncoated roofs to investigate the heat transfer on the roof with regards to the temperature reduction. Numerical results were compared with the field data. The performance of the solar photovoltaic module deployed on the rooftop was evaluated as well. The results demonstrate that the coated roof gives rise to a significant reduction in temperature, which enhances the thermal comfortability in the building. With the participation of the solar photovoltaic module, a total energy of 427.670 MW h/year could be fed into the national grid. The reduction in the power generation cost is accomplished with the joint application of the solar photovoltaic system and the roof coating.